1972
DOI: 10.1039/p19720002280
|View full text |Cite
|
Sign up to set email alerts
|

Scytalidin: a new fungitoxic metabolite produced by a Scytalidium species

Abstract: A new fungitoxic metabolite, designated scytalidin. was isolated from culture medium which had supported growth of Scytalidium sp., an imperfect fungus. The structure (3) of scytalidin (1 0-butyl-5,9,10,11 -tetrahydro-I 0hydroxy-4-pentyl-4H-cyclonona[1,2-c:5.6-c']difuran-l,3.6,8-tetraone) was established on the basis of spectrometric and chemical investigations. The metabolite is related structurally and biosynthetically to the nonadrides.A SPECIES of Scytalidium, FY strain, was observed by Ricard and his coll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
23
0
1

Year Published

1972
1972
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 0 publications
1
23
0
1
Order By: Relevance
“…Certains représentants du genre Scytalidium ont montré des propriétés antibiotiques intéressantes notamment vis-à-vis du F. annosus (KUNGSTROM et al, 1965 ;STRUNZ et al, 1972, STII/WËEE et al, 1973. In situ, RICARD (1975) ine, it is a boring at 1.30 m).…”
Section: -Isolement Dans Les Arbres Abattusunclassified
“…Certains représentants du genre Scytalidium ont montré des propriétés antibiotiques intéressantes notamment vis-à-vis du F. annosus (KUNGSTROM et al, 1965 ;STRUNZ et al, 1972, STII/WËEE et al, 1973. In situ, RICARD (1975) ine, it is a boring at 1.30 m).…”
Section: -Isolement Dans Les Arbres Abattusunclassified
“…In a recent paper Strunz et al (1) reported the isolation of several metabolites from a species of Scytalidiunz FY strain. The structure of one & of these was shown to be related to the nona- R2O OR3…”
mentioning
confidence: 99%
“…This phenomenon was used to devise a control method (Ricard et al, 1969). The effect observed as well as the activity against other wood-inhabiting microorganisms (Stillwell et al, 1973) could be ascribed to the presence of scytalidic acid (Overeem and Mackor, 1973) or scytalidin (Strunz et al, 1972). The stability of this antibiotic also explained the apparent long-term effect of Scytalidium inoculations (Ricard, 1975).…”
mentioning
confidence: 84%